Asymptotic Behavior of a Competition-Diffusion System with Variable Coefficients and Time Delays - Miguel Uh Zapata; Eric Avila Vales; Angel G. Estrella (Journal of Applied Mathematics)
A class of time-delay reaction-diffusion systems with variable coefficients which arise from the model of two competing ecological species is discussed. An asymptotic global attractor is established in terms of the variable coefficients, independent of the time delays and the effect of diffusion by the upper-lower solutions and iteration method.